Physical exercise activates a PVN–NAc oxytocin circuit to relieve stress-induced depressive-like behaviors - Jie Xia; Yong Zou; Yuqing Cui; Sen Zhang; Konglin Huo; Wenbin Liu; Zhuochun Huang; Qiang Zhang; Zhengtang Qi; Weina Liu (Proceedings of the National Academy of Sciences, 2025)
Physical exercise is known to reduce depression, but the underlying brain mechanisms remain unclear. Based on a chronic restraint stress model in mice, we showed that 4-wk treadmill exercise profoundly maintained normal neural activity in the nucleus accumbens (NAc), in association with the prevention of depressive-like behaviors. Microarray analysis conducted in the NAc revealed that the oxytocin (OT) receptor displayed the most significant differential expression, implying a crucial involvement of OT signaling in exercise-induced antidepressant effects. In vivo fiber photometry revealed disrupted OT release in the NAc and altered activity of OT neurons in the paraventricular nucleus (PVN) and their projections to the NAc in stressed mice, which were restored by exercise. Moreover, we found that stress-induced depressive-like behaviors were prevented by activation of the PVN–NAc OT circuit. Additional inhibition of the PVN–NAc OT circuit blocked the antidepressant effects of exercise in stressed mice. In summary, our findings reveal a critical role of the PVN–NAc OT circuit in regulating depressive-like behaviors, which is required for the antidepressant effects of exercise. This neural circuit mechanism provides an explanation for brain network adaptations upon exercise and also suggests a promising therapeutic target for depression.